Chipped stone (Scottish Historical and Archaeological Internet Reports, 2005)
A vast assemblage of worked and natural quartz, flint and other kinds of stone was recovered from, on, within, under and near the cairn at Olcote. In an interpretative sense the assemblage remains a little obscure. A range of deliberate deposits of lithic material can be identified, including the deliberate smashing of quartz pebbles, a raw material that may have had some associations with funerary contexts, during and/or after the construction of the cairn, which appears to have been carpeted with it. Finely made formal artefacts were also deposited into and under the cairn. These included types of objects that often had funerary associations. The area around the cairn included scatters of worked quartz and flint. It is possible that stone-working was attracted to this location by the presence of the cairn itself, or that the cairn was built in an area already significant for stone-working.